Estimation of intangible quality costs using neutrosophic AHP-TOPSIS, Neutrosophic Sets and systems - Yaité Pérez Mayedo; Yadira Velázquez Labrada; Néstor Miguel Álvarez Álvarez; Leonardo Rafael Pérez Molina; Maikel Leyva Vázquez; Shakila Devi G T (Neutrosophic Sets and Systems)
This study addresses the challenge of quantifying intangible quality costs (IQCs), which are inherently subjective and often overlooked in traditional quality cost management. We propose a novel hybrid framework that integrates the Neutrosophic Analytic Hierarchy Process (NAHP) with triangular neutrosophic numbers and Neutrosophic TOPSIS (NTOPSIS) with single-valued neutrosophic sets (SVNS) to evaluate and prioritize IQCs. The framework enables the aggregation of expert inputs, transforming qualitative risks—such as supplier mistrust and communication gaps—into quantifiable cost metrics. Applied to a steel mill’s, the methodology allowed to cuantificate the IQCs of the scrap reception activity. The study concludes that the framework’s structured yet adaptive nature provides organizations with a practical tool for prioritizing and mitigating intangible quality risks, overcoming the limitations of conventional methods. The results validate the importance of neutrosophy in the decision-making process under uncertainty in quality cost management.